Faunistic results from the 2nd Balkan OdonatOlogical Meeting – BOOM 2012, Serbia - Saša Rajkov; Damjan Vinko; Andrea Aranđelović (Natura Sloveniae)
As a part of the Balkan odonatological cooperation, the 2nd Balkan OdonatOlogical Meeting (BOOM 2012) was held in Vojvodina (Serbia). Altogether, between 7. and 12. 8. 2012, 24 localities were surveyed and 34 dragonfly species found. This represents more than half of the hitherto recorded dragonfly species for the country. Significant results include the second record and a new locality of Aeshna grandis for Serbia and the first confirmation of successful reproduction of Anax ephippiger in the country. New data on several species with a comparably low number of previously published records for Vojvodina, i.e. Somatochlora meridionalis, Cordulia aenea, Gomphus flavipes, Sympetrum flaveolum, Sympetrum vulgatum and Lestes dryas, is also presented and briefly discussed.